Gastrodiplomacy: How Indonesian Cuisine Shapes Bilateral Relations with Saudi Arabia (2017-2023) - Renta, Pebria Prakarsa; Putra, Addarsyah Dhia; Azzaahidi, Ibaadurrahman; Zauzah, Nino Zeh (Jurnal Hubungan Internasional, 2025)
This study aims to elucidate Indonesia’s strategic use of gastrodiplomacy in Saudi Arabia from 2017 to 2023, highlighting a soft diplomacy approach. By engaging in gastrodiplomacy, Indonesia intends to introduce its culinary heritage and enhance its international reputation. This strategic effort is undertaken collaboratively by the Indonesian government and Indonesian restaurateurs in Saudi Arabia. Utilizing the concepts of gastrodiplomacy and national interest, the research investigated the strategies deployed to promote Indonesian cuisine and the underlying governmental objectives. A descriptive-qualitative method was employed, with data collection achieved through a literature review. The findings revealed that the Indonesian government and food entrepreneurs have implemented gastrodiplomacy in Saudi Arabia through two primary strategies: opening various Indonesian restaurants and organizing Indonesian food events. Consequently, Indonesia’s national interests could be softly pursued through gastrodiplomacy. This paper offers recommendations for future research to assess the effectiveness of Indonesian gastrodiplomacy in Saudi Arabia, as well as the possibility of comparative studies with gastrodiplomacy efforts in other countries.